Behavioral Accounting and Control in Village Fund Management in Indonesia - Gaguk Apriyanto; Saman Abdul Azis; Thalita Ananda Putri (AKRUAL: JURNAL AKUNTANSI, 2024)
Research Background: This article examines the role of behavioral accounting in improving village fund management control in Indonesia. As public sector organizations face increasing demands for accountability and efficiency, understanding the psychological and behavioral aspects that influence financial decision-making becomes crucial. Behavioral accounting, which integrates insights from psychology and organizational behavior, offers a nuanced perspective on budgeting practices beyond traditional financial metrics. Introduction/Main Objectives: This study highlights the influence of morality, capabilities, and innovative work behavior on village fund management. Methods: Data collection was conducted by distributing questionnaires to village officials directly involved in village finances. The sample size for this study was 178 people, selected using a purposive sampling technique. The data analysis technique used in this study was multiple linear regression analysis using IBM SPSS 26. Results: The results indicate that morality, capabilities, and innovative work behavior of village officials have a positive effect on village fund management. Morality, capabilities, and innovative work behavior of village officials will be able to prevent fraud in village funds and improve accountability in village fund management. Conclusion: This research is expected to contribute to the implementation of sound village fund management in the reallocation and refocusing of the State Budget (APBN). Ultimately, this study proposes strategic implications for integrating behavioral insights into public financial management. This article contributes to the discourse on public sector accountability reform by emphasizing the human dimension of budget control.